ENVIRONMENT FRIENDLY STRATEGY TO INCREASE ANTIOXIDANT CONTENT AND PRODUCE OF SAUROPUS ANDROGYNUS - SHUBHA; K. Y. PRATHIBHA; A. C. MANJULA; NAYANA BHAT; R. SUHASINI (The Bioscan, 2011)
Sauropus androgynus is an important green leafy vegetable used in South India and is a rich source of antioxidants. A field trial was conducted wherein Sauropus androgynus was treated with biofertilisers Azospirillum, Bacillus megaterium, farm yard manure (FYM), vermicompost, combined treatment of all and compared with the control. The results obtained were analyzed for growth, enzymic and nonenzymic antioxidants.The study revealed that FYM treated plants showed significant increase in shoot length and number of leaves. There was a significant increase in non-enzymic antioxidants viz., carotenoids, ascorbic acid and total phenolics in FYM treated plants. Among enzymic antioxidants highest peroxidase activity and catalase activity was recorded in combined treatment. FYM treated plants also recorded maximum catalse activity.